Sharia economy, Islamic financial performance and factors that influence it: Evidence from Indonesia - Firman Menne; Sukmawati Mardjuni; Muhammad Yusuf; Muhlis Ruslan; A. Arifuddin; Iskandar Iskandar (Economies, 2023)
The contribution of SMEs to economic growth is supported by the development of the sharia economy by the government, making SMEs one of the main pillars in Indonesia's economic development. This study aimed to analyze the influence of the digital economy, financial literacy, human capital, the role of Islamic financial institutions, government support for strengthening the Islamic economy and the Islamic financial performance of SMEs in Makassar City, Indonesia. This study used a quantitative method with a survey approach. Data were obtained through questionnaires distributed to 350 respondents with a sampling method. The results of this study indicated that the strengthening of the sharia economy, the Islamic financial performance of SMEs, economic digitalization and financial literacy are determined by factors of human capital, the role of Islamic financial institutions and government support. Regarding human capital, the roles of Islamic financial institutions and government support affect the Islamic financial performance of SMEs with a coefficient of determination of 58.5%. Human capital, the role of Islamic financial institutions, government support and financial performance have a positive correlation with the strengthening of the sharia economy with a coefficient of determination of 71.6%. This study supports the improvement of government policies and the construction of financial facilities in improving the Islamic financial performance of SMEs and encourages the strengthening of the sharia economy in Makassar City, South Sulawesi, Indonesia. The limitation of this research is that the research object was only carried out on SMEs in Makassar City; thus, similar research can be increased at the national level to describe the strengthening of the sharia economy and the improvement of the financial performance of SMEs as a whole in Indonesia.
Keywords: 330; sharia economy; Islamic financial performance; digital economy; financial literacy